2019
DOI: 10.1097/ju.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Routine Prescription of Opioids for Post-Vasectomy Pain Control Associated with Persistent Use

Abstract: Purpose: The AUA (American Urological Association) Position Statement on opioid use recommends using opioids only when necessary. We sought to determine if routine prescribing of opioids is necessary for pain control after vasectomy, and if an association exists with persistent use. Materials and Methods: We retrospectively reviewed the charts of patients who underwent vasectomy in clinic between April 2017 and March 2018. Patients were stratified into 2 groups, including those initially prescribed opioids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Reassuringly, most urologists wrote for a small number of opioid tablets, with 66.7% prescribing 5–10 tablets. Barham et al found that most urologists prescribed a range of 5–20 opioid tablets for post‐vasectomy pain control (Barham et al, 2019); our data suggest that this is closer to the 5–10 range versus 10–20.…”
Section: Discussionmentioning
confidence: 46%
“…Reassuringly, most urologists wrote for a small number of opioid tablets, with 66.7% prescribing 5–10 tablets. Barham et al found that most urologists prescribed a range of 5–20 opioid tablets for post‐vasectomy pain control (Barham et al, 2019); our data suggest that this is closer to the 5–10 range versus 10–20.…”
Section: Discussionmentioning
confidence: 46%
“…is notably lower than previous reports detailing outcomes in urologic surgery populations, where it has been estimated that 6-9% of patients show evidence of persistent use at three-months after surgery (13,18,19). Using a similar dataset and rigorous methodology, Hosier and colleagues found a 9% rate of persistent opioid use at three-months postoperatively (after initial perioperative exposure) in a cohort of nearly 102,000 patients who underwent treatment for urolithiasis from 2013-2017 (20).…”
Section: Editorial Commentarymentioning
confidence: 83%
“…More alarmingly, there are many patients who then have excess narcotics, which are unlikely to be disposed of properly and may be abused in the future by patients or their acquaintances (25). Barham and co-workers found that routine postvasectomy opioid prescriptions resulted in 7.8% of previously opioid-naïve patients having persistent opioid use 90 days after vasectomy (26). A better pain management strategy would be to emphasize nonsteroidal anti-inflammatory drugs.…”
Section: The Patient Experiencementioning
confidence: 99%